Managing for people who hate managing : be a success by being yourself (Berrett-Koehler Publishers : O'Reilly, 2015)
"This video lesson recaps key concepts such as: identify and accept your natural temperament, capitalize on your strengths, shift expectations to yourself, focus on cues, and follow your instincts."--Resource description page